Characterization and treatment of tunneling wastewater using natural and chemical coagulants - Mehrdad Ghorbani Mooselu; Helge Liltved; Naureen Akhtar (Water Science and Technology, 2023)
Particles are a concern regarding tunneling wastewater, but gaps remain in understanding metal(loid)s content and coagulation efficiency. In this research, characterization of the wastewaters before and after treatment was investigated by chemical analysis and various techniques for particle characterization. Then, laboratory work was conducted to evaluate effectiveness of sedimentation and use of coagulants to remove particles and particle-associated contaminants. Both natural (chitosan) and chemical coagulants (ferric chloride sulfates and polyaluminium chloride solution), were applied in a jar test system. The results indicated that short-time sedimentation alone substantially reduced the particle content and particle-associated pollutants, including metal(loid)s, while subsequent chemical coagulation was required to comply with discharge limits. The optimum dosages of chitosan, PIX, and PAX for water 1 after pre-treatment (15 min sedimentation) were 1 mg/L, 3 mg Fe/L, and 3 mg Al/L, respectively, while a dosage of 2 mg Al/L gave the best results in water 3. Furthermore, chemical coagulation significantly decreased the volume density of particles in the diameter range of 1–100 μm, showing that coagulants are efficient for the removal of smaller particles not removed by conventional sedimentation. HIGHLIGHTS Characterization and treatment of tunneling wastewater were considered.; The size distribution, shape, and morphology of the particles were analyzed.; The application of both natural and chemical coagulants was assessed.; The proposed method shifted particle size from coarser fractions to finer fractions.; Chemicals decreased the particle volume showing coagulant efficiency.;